Kepribadian Ekstrovert–Introvert dalam Kelancaran Berbicara Bahasa Arab: Analisis Konten dalam Perspektif Psikolinguistik - Azmy, Muhammad Ulul; Munip, Abdul (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2025)
Abstract This article aims to analyse the influence of extrovert-introvert personality on speaking fluency in learning Arabic as a foreign language through psycholinguistic perspective and content analysis method. The study is conducted by systematically reviewing scientific literature that discusses the relationship between personality, speech production, and oral performance. The results show that personality types affect conceptualisation, formulation and articulation processes differently, with extroverts excelling in fluency, while introverts are more accurate. In addition, this study also reveals the importance of teacher strategies in shaping students' confidence through approaches such as Suggestopedia and positive affirmations. The contribution of this study lies in proposing personality-adaptive learning models as well as building a classroom system that supports the development of speaking courage. Keywords: personality, extrovert, introvert, speaking fluency, confidence, Arabic, psycholinguistics.